2015
DOI: 10.1089/brain.2014.0273
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Variations in Functional Connectivity of the Resting State Default Mode Network in Mild Traumatic Brain Injury

Abstract: A definitive diagnosis of mild traumatic brain injury (mTBI) is difficult due to the absence of biomarkers in standard clinical imaging. The brain is a complex network of interconnected neurons and subtle changes can modulate key networks of cognitive function. The resting state default mode network (DMN) has been shown to be sensitive to changes induced by pathology. This study seeks to determine whether quantitative measures of the DMN are sensitive in distinguishing mTBI subjects. Resting state functional m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 57 publications
11
45
1
Order By: Relevance
“…Four of the significant changes in rsFNC observed in our analysis involved connectivity between cerebellum and sensorimotor RSNs. A similar result has been observed before by Nathan and coworkers 24 in which the functional connectivity between cerebellum and SMA showed an increase in patients with TBI. Another study found functional connectivity of the cerebellum among those correlated with post-concussive complaints.…”
Section: Alterations Of Rsfncsupporting
confidence: 90%
See 2 more Smart Citations
“…Four of the significant changes in rsFNC observed in our analysis involved connectivity between cerebellum and sensorimotor RSNs. A similar result has been observed before by Nathan and coworkers 24 in which the functional connectivity between cerebellum and SMA showed an increase in patients with TBI. Another study found functional connectivity of the cerebellum among those correlated with post-concussive complaints.…”
Section: Alterations Of Rsfncsupporting
confidence: 90%
“…21,22 Other areas where connectivity disruption has been found in subjects with mTBI include the primary visual, hippocampal, and dorsolateral prefrontal cortexes 23 as well as increased connectivity in the cerebellum. 24 Studying the brain in a more comprehensive way, it has been suggested that stronger connectivity among functional brain networks is a normal response to brain injury. 25 Collectively, these results suggest that methods to exploit resting state functional connectivity as a biomarker should be comprehensive rather than specific when including relevant brain areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2013) reported increased connectivity between salience and task‐positive networks. The connectivity between cerebellum and the SMA has been found to be stronger in mTBI patients (Nathan et al., 2014; Vergara et al., 2015). The evidence points to a pattern of increased connectivity involving salience, sensorial, auditory, and visual areas (Mayer et al., 2011, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Connectivity changes in the supplementary motor area and the cerebellum have been reported by Nathan et al. (2014) using a seed‐based approach. While changes in the DMN of mTBI patients were found in the study by Vakhtin et al.…”
Section: Introductionmentioning
confidence: 99%